2016
DOI: 10.4103/2249-4863.184632
|View full text |Cite
|
Sign up to set email alerts
|

A household survey to assess community knowledge, attitude and practices on malaria in a rural population of Northern India

Abstract: Introduction:An extensive search on PubMed reveals very little in terms of evidence regarding the current knowledge, attitude, and practices (KAP) of the population in general and rural population, in particular, in this part of the country. Therefore, a study was conducted with the aim to assess the communities’ knowledge of malaria transmission, recognition of signs and symptoms, treatment seeking.Materials and Methods:A stratified two-stage design was used to conduct a house-to-house survey using a semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
7
8
1
Order By: Relevance
“…This finding is consistent with findings in other studies from different malaria endemic regions around the world which indicates that Community Health Workers are frequently in contact with people [ 21 , 25 , 26 ]. This is in contrast to findings from a recent study conducted in Saudi Arabia, India and Uganda that reported the social media as the primary source of malaria information [ 20 , 27 , 28 ]. Access to Community Health Workers and communication facilities had previously been reported to play an important role in prevention and control of malaria [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with findings in other studies from different malaria endemic regions around the world which indicates that Community Health Workers are frequently in contact with people [ 21 , 25 , 26 ]. This is in contrast to findings from a recent study conducted in Saudi Arabia, India and Uganda that reported the social media as the primary source of malaria information [ 20 , 27 , 28 ]. Access to Community Health Workers and communication facilities had previously been reported to play an important role in prevention and control of malaria [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This observation supports ndings of another study conducted in Tanzania, which reported that more than 80% of school children had knowledge on malaria transmission (Sumari et al, 2016). This nding is comparable with the report from the study in Swaziland (Hlongwana et al, 2009), Northwest Tanzania (Mazigo et al, 2010), India (Mahesh et al, 2014), Northern India (Gupta et al, 2016) and Mexico (Rodriguez et al, 2003). This situation is higher compared with that reported by Legesse et al (2017), which was observed that about three forth (75.1%) of respondents had correct understanding of mode of transmission of malaria,which also corroborate studies in Nigeria in which 74.3% of the study participants has mentioned mosquito bite as mode of malaria transmission (Singh et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Knowledge of mosquito behavior (resting and breeding places and feeding time) is important to take appropriate malaria preventive actions and for the proper use of ITNs. Observations regarding breeding sites of mosquitoes were 265(67.9%), 80(20.5%), 41(10.5%) and 4(1.0%) of the study participants mentioned that stagnant water, tall grass, bushes and running water respectively.The results are consistent with some other studies, which have Knowledge regarding breeding and resting places of mosquitoes in India (Gupta et al, 2016) and in Shashogo District, Southern Ethiopia (Fuge et al, 2015). This is low when compared with the report from the study conducted in Tepi Town, Sheka Zone, Southwestern Ethiopia, most of the community members were aware that the mosquito breeds in stagnant water which is (96.4%) (Haile et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Implementation of culturally appropriate, sustainable, and effective interventions is crucial for the success of vector control strategies. Since, India stands next to Africa in the number of malaria cases with an observed increase of cases in urban areas, stringent measures of surveillance followed by control and follow up strategies have to be executed and monitored to reduce the disease burden [ 24 , 25 ]. The present survey revealed many factors, which influenced the malaria incidence/prevalence in the study site in a significant way.…”
Section: Discussionmentioning
confidence: 99%